Lycium barbarum glycopeptide promotes neuroprotection in ET-1 mediated retinal ganglion cell degeneration - Yamunadevi Lakshmanan; Francisca Siu Yin Wong; Kwok-Fai So; Henry Ho-Lung Chan (Journal of Translational Medicine, 2024)
Abstract Background Vascular dysregulation is one of the major risk factors of glaucoma, and endothelin-1 (ET-1) may have a role in the pathogenesis of vascular-related glaucoma. Fruit extract from Lycium Barbarum (LB) exhibits anti-ageing and multitarget mechanisms in protecting retinal ganglion cells (RGC) in various animal models. To investigate the therapeutic efficacy of LB glycoproteins (LbGP) in ET-1 induced RGC degeneration, LbGP was applied under pre- and posttreatment conditions to an ET-1 mouse model. Retina structural and functional outcomes were characterised using clinical-based techniques. Methods Adult C57BL/6 mice were randomly allocated into four experimental groups, namely vehicle control (n = 9), LbGP-Pretreatment (n = 8), LbGP-Posttreatment (day 1) (n = 8) and LbGP-Posttreatment (day 5) (n = 7). Oral administration of LbGP 1 mg/Kg or PBS for vehicle control was given once daily. Pre- and posttreatment (day 1 or 5) were commenced at 1 week before and 1 or 5 days after intravitreal injections, respectively, and were continued until postinjection day 28. Effects of treatment on retinal structure and functions were evaluated using optical coherence tomography (OCT), doppler OCT and electroretinogram measurements at baseline, post-injection days 10 and 28. RGC survival was evaluated by using RBPMS immunostaining on retinal wholemounts. Results ET-1 injection in vehicle control induced transient reductions in arterial flow and retinal functions, leading to significant RNFL thinning and RGC loss at day 28. Although ET-1 induced a transient loss in blood flow or retinal functions in all LbGP groups, LbGP treatments facilitated better restoration of retinal flow and retinal functions as compared with the vehicle control. Also, all three LbGP treatment groups (i.e. pre- and posttreatments from days 1 or 5) significantly preserved thRNFL thickness and RGC densities. No significant difference in protective effects was observed among the three LbGP treatment groups. Conclusion LbGP demonstrated neuroprotective effects in a mouse model of ET-1 induced RGC degeneration, with treatment applied either as a pretreatment, immediate or delayed posttreatment. LbGP treatment promoted a better restoration of retinal blood flow, and protected the RNFL, RGC density and retinal functions. This study showed the translational potential of LB as complementary treatment for glaucoma management.